Professional Ethics of Community Rabbis and Religious Scholars in Judaism - Rashi, Tsuriel (2022)
This article represents a first attempt to collect and analyze texts written by halakhic authorities throughout the generations that deal with the professional ethics of rabbis and religious scholars. From these texts, we understand that the ideal rabbi embodies a combination of professionalism, humility, and a shouldering of his responsibilities as a religious leader. Respectful and dignified conduct when he engages with his community is the mark of his professional vocation. I also look at the appropriate relationship between a community and its rabbi, from his appointment through the way he fulfills his obligations and the circumstances around his parting from his congregation.
Keywords: Professional Ethics; Halakhah; Rabbis; Jewish ethics